STUDENTS’ REFLECTION ON THE EXPERIENCE IN ONLINE SCHOOL INTERNSHIP PROGRAM BASED ON EXPERIENTIAL LEARNING - Aji, Gregorius Punto (Sanata Dharma University Yogyakarta, 2022)
Program Pengalaman Lapangan (School Internship Program), abbreviated as PLP, is an obligatory course in the curriculum of study programs under the faculty of teachers training and education. It adopts an experiential field learning to provide comprehensive, direct, and real experiences in school. A long-term goal is set to develop professional teacher competencies. In the Covid-19 pandemic, PLP has been implemented online. This research aimed to analyse the students’ reflections on experiences in online PLP on School Environment to find out to what extent they understand the school environment, good and inspirational experiences, meaning or values that were developed by students, intentions for self-development that arouse based on the experience and reflections, obstacles faced by students and how to solve them. This research was a qualitative research. The results of the study indicated that students’ experiences in getting to know the school environment were included in the good category, students gained various good and inspirational experiences, experiences in overcoming obstacles that arose due to the pandemic, developed meaning or values, and developed intentions for self-development as a teacher candidate. Thus, the meaningful learning cycle based on experiential learning was experienced by the students participating in the online PLP.